POTENSI ENERGI KINETIK ARUS PASANG SURUT DI SELAT TOYAPAKEH, BALI - Fadli Kaththab Mukarto, Imam
The research of potential tidal kinetic energy calculation has been carried in Toyapakeh Strait, Bali, Indonesia. Current dynamics simulated using Delft3D-Flow hydrodynamic model with 8 tidal constituents (M2, S2, K1, O1, N2, K2, P1, and Q1) from TPXO 7.2 Satelite with assumption vertical speed is the same (2D). Bathymetry data was taken from GEBCO (General Bathymetric Chart of The Ocean) combined with BIG (Badan Informasi Geospasial) and P3GL (Pusat Penelitian dan Pengembangan Geologi Kelautan) field measurement in 2015. The model was run for a period of 25 days (August 10th – September 3th). Then, we calculated potential of kinetic energy using Fraenkel equation and Gorlov Helical Turbine’s performance that can produce electrical power from ocean current with minimum speed (cut-in speed) of 0.5 m/s. The result of simulation shows that total electrical power potential in one tide cycle reach its maximum value in the Point B (8.7° S - 115.4633° E), it reachs 144.614 kW in spring tide and 31.433 kW in neap tide. Under simulation turbine can produced electrical power for 12 days with total electrical power reaches 986.882 kW. These electrical powers are produced by using Gorlov Helical Turbine with 0.6 m diameter and 0.86 m height.